Metabolic response to an inflammatory challenge in pigs divergently selected for residual feed intake. Issue 2 (1st February 2016) - Merlot, E.; Gilbert, H.; Le Floc'h, N.
Abstract: Selection for residual feed intake (RFI), which is used to select animals for feed efficiency, also influences nutrient partitioning between growth and maintenance functions. This study was designed to investigate if selection for reduced RFI can alter the trade-off between growth and immunity and contributes to differences in metabolic responses to an inflammatory challenge. Piglets from 2 lines divergently selected on RFI (low: RFI −, n = 10, and high: RFI +, n = 11) were challenged at 55 d of age (on d 0) with complete Freund's adjuvant (CFA) to induce a noninfectious pneumonia. Plasma haptoglobin and nutrient concentrations (in fasted state and 2 h after feeding) were determined from d −1 to d 7, and tissue protein metabolism was determined on d 8. Haptoglobin concentrations were greater from d 1 to d 7 relative to d −1 ( P < 0.01). Feed intake was less on d 1 than on the other days ( P < 0.001), as was total AA plasma concentrations at fasted state ( P < 0.05). Fasted concentrations of His ( P = 0.06) and Trp ( P = 0.05) tended to be less, those of Val were less ( P < 0.05), and fed concentrations of Lys were increased ( P < 0.05) on d 7 compared to d −1. Uremia was less on d 7 than on d −1 at fasted state ( P < 0.05), whereas it did not vary at fed state ( P > 0.1). Fasted glucose and insulin plasma concentrations were stable across days ( P > 0.1). In the fed state and in only RFI + pigs, glucose concentration was greater on d 1 than on d 3, 5, and 7 ( P < 0.05). Total AA, Gln, Ile, Leu, Pro ( P < 0.05), and hydroxyproline ( P = 0.07) were less in RFI − than RFI + pigs at fed state, whereas Ala and Gly were less in RFI − pigs at fasted and fed states ( P < 0.05). Citrulline ( P < 0.05) and Met ( P < 0.01) concentrations were greater in RFI − than RFI + pigs in the fasted state, whereas Asp was greater in RFI − pigs in both fasted and fed states ( P < 0.05). On d 8, liver and LM protein synthesis tended to be lower ( P = 0.07 and 0.09, respectively) and liver calpain activity was greater ( P = 0.07) in RFI − than RFI + pigs. Liver and LM proteasome did not differ between lines ( P > 0.1). The metabolic differences between lines were not associated with differences in feed intake, ADG between d −1 and d 8, and haptoglobin concentration ( P > 0.1). Thus, it seems that that, using different metabolic strategies, both lines coped similarly with the CFA challenge. Contrary to our hypothesis, this experiment showed, in young pigs, no advantage of RFI + animals in response to an inflammatory challenge.